Analysing travel mode and airline choice using latent class modelling: A case study in Western Australia. (July 2020) - Zhou, Heng; Norman, Richard; Xia, Jianhong(Cecilia); Hughes, Brett; Kelobonye, Keone; Nikolova, Gabi; Falkmer, Torbjorn
Highlights: Estimating travel mode and airline choice using air and non-air passengers' stated preference data. Accommodating passengers' preference heterogeneity using latent class models. Investigating the differences in travel mode choice, socio-demographics and trip characteristics among passenger segments. Examining willingness to pay (WTP) of the travellers. Abstract: This paper investigates travel mode and airline choice using stated-preference data. Both air and non-air passengers' data were collected in Western Australia, which allows easier generalisability of the findings to a wider population. A market segmentation approach, using latent class modelling, was applied to identify passenger segments. The results shown a significant difference between identified segments in terms of demographics, economics and trip characteristics. One segment, comprising travellers with higher income and more frequent business travellers, was sensitive to service-factors. The other, comprising personal travellers with lower incomes, placed higher sensitivity on price. The findings highlight the importance of understanding mode choice behaviour based on market segmentation and provides insights to policy-makers and airlines for developing more effective polices and strategies.